A project feasibility study for a dress shop operator - Garvida, Cheryl M.
The project concerns the establishment of a single proprietorship, dress operation at 75 A. Luna St. Project 4, Quezon City. The shop shall be operated under the firm name CLOTHES TALK, and shall be owned and operated by Cheryl M. Garvida, a B.S. Clothing Technology candidate. The proposed project shall undertake the manufacture of ready-to-wear and custom-made dresses on a small scale volume, principally to cater to the female residents of Barangay Bagumbahay, aging 15 to 49 years old. The economic prospects for the country has been encouraging enough to promote domestic investments such as this proposed business venture. It is hoped that the project shall provide positive contribution to the livelihood program of the government.